2020
DOI: 10.1101/2020.07.25.220673
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A unified atlas of CD8 T cell dysfunctional states in cancer and infection

Abstract: CD8 T cells play an essential role in defense against viral and bacterial infections and in tumor immunity. Deciphering T cell loss of functionality is complicated by the conspicuous heterogeneity of CD8 T cell states described across different experimental and clinical settings. By carrying out a unified analysis of over 300 ATAC-seq and RNA-seq experiments from twelve independent studies of CD8 T cell dysfunction in cancer and infection we defined a shared differentiation trajectory towards terminal dysfunct… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 84 publications
2
26
2
Order By: Relevance
“…Discrepancies regarding CD8 + T ex stability in the presence/absence of antigen may be due to the frequency and quality of TCF-1 + stem-like cells at hand. A unified atlas of 12 studies spanning cancer and chronic viral infection has recently revealed that bifurcation of memory commitment from a dysfunctional program occurs early (in less than 7 days following antigen encounter) ( 61 ). With preclinical cancer models, the time of initial antigen encounter is less controlled for compared to viral infection.…”
Section: Dawn Of Stem-like Precursors and Progenitors Of Exhausted Cd8 + T Cellsmentioning
confidence: 99%
“…Discrepancies regarding CD8 + T ex stability in the presence/absence of antigen may be due to the frequency and quality of TCF-1 + stem-like cells at hand. A unified atlas of 12 studies spanning cancer and chronic viral infection has recently revealed that bifurcation of memory commitment from a dysfunctional program occurs early (in less than 7 days following antigen encounter) ( 61 ). With preclinical cancer models, the time of initial antigen encounter is less controlled for compared to viral infection.…”
Section: Dawn Of Stem-like Precursors and Progenitors Of Exhausted Cd8 + T Cellsmentioning
confidence: 99%
“…Next, we focused on the early programming of exhaustion by comparing D8 scATAC-seq phenotypes in Arm and Cl13 infection (Figure S3A). As previously described, memory precursor cells (T mp ) are present at D8 in Arm infection and cluster with an early Tex prog population present at D8 in Cl13 infection that expresses Tox and Tcf7 (herein referred to as precursor exhausted -Tex prec ), but these subsets were relatively infrequent compared to the effector populations in both infection models (1.4% of D8 cells in Arm infection, 3.3% of cells at D8 in Cl13 infection) [14,41]. We first compared the gene expression and chromatin state programs of T mp and Tex prec subsets, which revealed strong exhaustion-and interferon-induced programs in Tex prec , as expected (Figure S3B, S3C and S3D, Table S9).…”
Section: Resultsmentioning
confidence: 89%
“…Recent studies have reported that development of T cell exhaustion during chronic infection and cancer occurs in a multistep fashion, revealing distinct subtypes with unique transcriptional and epigenetic dynamics, as well as their ability to respond to immune checkpoint blockade (Im et al, 2016;Philip et al, 2017;Satpathy et al, 2019;Siddiqui et al, 2019;Jansen et al, 2019;Miller et al, 2019;Beltra et al, 2020;Pritykin et al, 2021).…”
Section: Discussionmentioning
confidence: 99%